Altered Cellular Protein Quality Control System Modulates Cardiomyocyte Function in Volume Overload-Induced Hypertrophy - Kamilla Gömöri; Melissa Herwig; Roua Hassoun; Heidi Budde; Nusratul Mostafi; Simin Delalat; Suvasini Modi; Merima Begovic; Tamara Szabados; Judit Pipis; Nikolett Farkas-Morvay; István Leprán; et al. (MDPI AG, 2022)
Volume-induced hypertrophy is one of the risk factors for cardiac morbidity and mortality. In addition, mechanical and metabolic dysfunction, aging, and cellular redox balance are also contributing factors to the disease progression. In this study, we used volume overload (VO), which was induced by an aortocaval fistula in 2-month-old male Wistar rats, and sham-operated animals served as control. Functional parameters were measured by transthoracic echocardiography at termination 4- or 8-months after VO. The animals showed hypertrophic remodeling that was accompanied by mechanical dysfunction and increased cardiomyocyte stiffness. These alterations were reversible upon treatment with glutathione. Cardiomyocyte dysfunction was associated with elevated oxidative stress markers with unchanged inflammatory signaling pathways. In addition, we observed altered phosphorylation status of small heat shock proteins 27 and 70 and diminished protease expression caspases 3 compared to the matched control group, indicating an impaired protein quality control system. Such alterations might be attributed to the increased oxidative stress as anticipated from the enhanced titin oxidation, ubiquitination, and the elevation in oxidative stress markers. Our study showed an early pathological response to VO, which manifests in cardiomyocyte mechanical dysfunction and dysregulated signaling pathways associated with enhanced oxidative stress and an impaired protein quality control system.